MODEL PENERAPAN AKUNTANSI SEKTOR PUBLIK UNTUK MENCEGAH FRAUD PADA SEKTOR PUBLIK DI ERA DIGITAL - DIAN KRISTIYANI; HAMIDAH HAMIDAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to find and describe the characteristics of fraud that occur in the public sector in the digital era and develop models of application of Public Sector Accounting to prevent fraud that occurs in the public sector in the digital age. The research carried out is a literature review study sourced from articles in accordance with the research topic for further analysis. The results showed that the characteristics of fraud in the public sector that occurred in the digital era include the use of misconceptions regarding the role of digital technology in the implementation of public accounting tasks, the utilization of digital technology to optimize opportunities for fraud, exploiting problems in human error and lack of knowledge in the use of technology. digital, using digital technology products, to carry out fraud. Application of Public Sector Accounting can prevent fraud in the public sector in the digital era if implemented by considering several factors that influence fraud, such as performance accountability, and accompanied by the application of fraud prevention methods which include technical strategies, two paradigm approaches, and preventive strategies.